Integration of Controlling Tools into Risk Management of International Financial Operations - Kryshtal, Halyna; Lytovchenko, Ruslan; Vasylkonova, Elina (Ways to Improve Construction Efficiency, 2025)
The article examines the theoretical, methodological, and applied aspects of integrating controlling tools into the risk management system of international financial operations under conditions of increasing global instability and the digital transformation of the economy. The relevance of the topic is driven by the growing volatility of international financial markets, the increasing complexity of financial flows, and the rising impact of currency, credit, operational, and systemic risks on the activities of international economic entities. The study reveals the essence of controlling as an integrated system of information and analytical support for managerial decision-making, combining planning, analysis, control, and forecasting functions. It is substantiated that the use of controlling tools improves the quality of financial process management, ensures timely risk identification, and facilitates the development of effective risk mitigation mechanisms. Special attention is given to the classification of controlling tools according to functional areas of risk management, including strategic analysis, operational control, financial planning, analytical assessment, and digital monitoring. Within the framework of the study, controlling tools are integrated into the risk management system of international financial operations, which allows for the formation of a comprehensive approach to ensuring the financial stability of international business entities. It is demonstrated that the application of modern information technologies, in particular ERP and BI systems, significantly enhances the effectiveness of controlling and ensures the promptness of managerial decision-making. The results obtained indicate that the integration of controlling tools into the risk management system contributes to increasing the adaptability of financial systems to external shocks, reducing uncertainty, and strengthening financial stability in the context of global transformations. The practical significance of the study lies in the possibility of applying the proposed approaches to improve the management of international financial operations at the level of enterprises and financial institutions.